Centrifugation, Storage, and Filtration of Olive Oil in an Oil Mill: Effect on the Quality and Content of Minority Compounds - Alfonso M. Vidal; Sonia Alcalá; Antonia de Torres; Manuel Moya; Francisco Espínola (Journal of Food Quality)
Centrifugation, storage, and filtration of olive oil were evaluated in an oil mill to determine their effect on the final quality of virgin olive oil. The main functions of these processes are to clarify the olive oil by removing water, solids, and other possible suspended particles. Although some changes were detected in the oil quality parameters after these processes, all the samples were extra virgin olive oil. The phenolic and volatile compound content of the olive oil was influenced by vertical centrifugation processing. Significantly, vertical centrifugation led to a 53% reduction in ethanol content. Oil storage before filtration resulted in a significant increase of around 30% in the peroxide index, while the antioxidant capacity decreased by 78%. Comparison of the results for filtered and unfiltered oil samples revealed that the most significant change was the reduction in the photosynthetic pigment content, with a decrease of around 50% in chlorophyll. Due of all this, the conditions applied in vertical centrifugation and the time of storage of the olive oils should be further controlled, enabling cleaning and decantation but avoiding the reduction of the antioxidant capacity and the content of phenolics compounds.